Exploring climate Impacts on rural sanitation and hygiene in Burkina Faso - R. Iyer (2022)
A conference contribution for the 1st Water-WISER Early Career Researcher Conference, Transdisciplinary Global Perspectives on Water and Waste Services, held at Loughborough University 21 - 23 June 2022.